Tanggung jawab hukum driver shopee terhadap kerusakan dan kehilangan barang dalam pengiriman - Ramadani, Naina Alfiah (Maliki Interdisciplinary Journal, 2025)
Freight transportation in Indonesia includes land, sea, and air routes. The need for freight transportation has resulted in the emergence of transportation service companies on all three routes. Shopee Express is a freight transportation service company that is legally authorized under the Commercial Postal Service, as stated in Article 18 Paragraph (1) of Law Number 38 of 2009 concerning Post. This study seeks to evaluate the effectiveness of product delivery on Shopee Express and the company’s responsibility for damage and loss that occurs during delivery. This study uses a qualitative research method, using descriptive and inductive methodologies. Qualitative research is used to examine the attributes of natural events, with researchers as the main instrument. The results of the study indicate that Shopee Express has full responsibility for delays, damage, and loss of products during delivery, which requires an apology for the delay and compensation for the monetary value of the goods if damage or loss occurs.